Preoperative ANemiA among elderly undergoing Major Abdominal surgery (PANAMA) is associated with early postoperative morbidity and worse quality of life outcomes - Hairil Rizal Abdullah; Celestine Jia Ling Loh; Eunice Jie Yi Kok; Brenda Pei Yi Tan; Hanis Abdul Kadir; Phui-Sze Au-Yong (Scientific Reports)
Abstract Preoperative anemia is associated with poor outcomes, but less is known about its impact on quality of life (QoL). This study investigates the association between preoperative anemia and QoL in elderly undergoing major abdominal surgery. This prospective observational study was conducted from 2017 to 2021 in a tertiary hospital’s preoperative anesthesia clinic. QoL outcomes were assessed using the EuroQol 5-Dimension 3-Level (EQ-5D-3L) and the EuroQol-Visual Analogue Scale (EQ-VAS). Data was collected at baseline, 1-, 3-, and 6-month postoperatively. Patients were included if they were 65 years or older, could provide written informed consent and were planned for elective major abdominal surgery. Patients were excluded if they were going for organ transplant surgery. A total of 469 patients were analyzed, of which 176 (38%) had anemia. There was no significant difference across varying anemia severity in EQ-5D-3L dimensions of mobility, self-care, usual activities, and pain/discomfort. Moderate-to-severe anemic patients generally have more issues across EQ-5D-3L dimensions. At baseline, these patients exhibited more issues with self-care (3%), pain/discomfort (13%), and anxiety/depression (19%), along with a lower mean EQ-VAS score of 77. However, there was a significant improvement in mobility, usual activities, and pain/discomfort over time. EQ-VAS score significantly improved for all groups of patients over time. The dimensions of EQ-5D-3L and EQ-VAS scores improved as the severity of anemia decreased. Preoperative anemia is associated with a significant decrease in QoL based on EQ-VAS. Recognizing and managing preoperative anemia may improve the recovery of elderly patients undergoing major abdominal surgery.